2015
DOI: 10.1111/jocn.12952
|View full text |Cite
|
Sign up to set email alerts
|

Modified early warning scoring (MEWS): evaluating the evidence for tool inclusion of sepsis screening criteria and impact on mortality and failure to rescue

Abstract: Development of all-cause illness screening tools, including sepsis, is imperative. The clinical picture may be quantified with scoring tools to assist nurses' clinical decision-making, thus leading to improved outcomes and decreased incidence of failure to rescue. Clinical outcomes of interest should be measured and reported in peer-reviewed literature to disseminate the impact on clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 20 publications
(33 reference statements)
1
33
0
Order By: Relevance
“…In addition to their potential use following an ICU admission, wearables may also play a role in monitoring inpatients for signs of clinical deterioration, so as to identify as soon as possible any patient needing a higher level of care. Early Warning Systems (EWS) have been developed to address a “failure to rescue” problem, in which critical illness is identified too late [ 21 ]. Wearable devices stand to enhance data collection and monitoring both prior to and following an ICU admission, and as such is of growing importance in critical care research.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to their potential use following an ICU admission, wearables may also play a role in monitoring inpatients for signs of clinical deterioration, so as to identify as soon as possible any patient needing a higher level of care. Early Warning Systems (EWS) have been developed to address a “failure to rescue” problem, in which critical illness is identified too late [ 21 ]. Wearable devices stand to enhance data collection and monitoring both prior to and following an ICU admission, and as such is of growing importance in critical care research.…”
Section: Discussionmentioning
confidence: 99%
“…A large observational study with hospitalized patients has shown that 9% had at least one clinically abnormal vital sign or adverse event in early stages of admission (Buist, Bernard, Nguyen, Moore, & Aderson, 2004). Mortality rates have been associated with signs missed during admission and hospitalization (Roney et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In conjunction with an academic‐clinical partnership, a team of frontline nurses, led by the hospital sepsis coordinator and mentored by a nurse scientist systematically searched and evaluated the scientific literature to validate key components of existing MEWS tools for inclusion of sepsis criteria. The details and results of this process and findings from phase one of the project have been published elsewhere . Organizational approval for the evidence‐based quality improvement project followed institutional policy and processes.…”
Section: Methodsmentioning
confidence: 99%